Digital Marketing and its Influence on Customer Loyalty of a Digital Training Center. Trujillo, 2024 - Bermúdez Mauricio, Leyner Brayan; Sandoval García, Franco; Mendoza Castillo, Alvaro Larry Luis Felipe (LACCEI, 2025)
Abstract – The objective of this research is to determine the influence of digital marketing on customer loyalty of a digital training center in Trujillo during the year 2024. The independent variable Digital Marketing was analyzed with its Brand Awareness, Engagement and Funnel dimensions. Sales, and the dependent variable Customer Loyalty with the dimensions Personalization, Differentiation and Satisfaction. The study is of an applied type, with a quantitative approach, non-experimental design and cross-sectional. The population was made up of 400 frequent students from the company’s database, using simple random sampling that resulted in a sample of 197 clients. Data collection was carried out through surveys, using a questionnaire as an instrument. The results indicated a coefficient of determination of 0.71, confirming that this has considerable value between digital marketing and customer loyalty.